O efeito da personalidade no sucesso dos projetos remotos internacionais: o papel mediador da inteligência cultural - Simplicio, Joelma Maria Pereira (2024)
The internationalization of organizations and the pursuit of new business opportunities have increased involvement in international projects, challenging companies to navigate the complexities of various cultural contexts. This reality demands that professionals collaborate with individuals from different backgrounds and ethnicities, posing notable challenges, particularly for international project managers who face intercultural dynamics. In this context, cultural intelligence emerges as an essential skill, standing out as a fundamental competency for facilitating interactions in multicultural environments. Simultaneously, research highlights the importance of personality traits, especially in remote international project managers. However, despite the significance of the topic, few studies have addressed the relationship between personality traits, cultural intelligence, and performance in the context of international projects. Therefore, the objective of this study is to investigate the relationship between project managers' personalities and project success, with an emphasis on the perceived impact on the team and clients, analyzing the mediating effect of cultural intelligence in this relationship. To this end, a quantitative approach was adopted, applying an online questionnaire to international project managers, using three validated scales: the project success scale, the Big Five personality scale, and the reduced CQS scale. The results indicate that the traits of openness to experience and conscientiousness, when mediated by cultural intelligence, are essential and amplify performance in diverse contexts, supporting previous studies on the relevance of cultural intelligence in managing multicultural teams and stakeholder satisfaction. In contrast, traits such as extraversion, agreeableness, and emotional stability did not show significant relationships with the team or clients in this study, highlighting the particularity of international projects, characterized by high cultural diversity. This study contributes to theory by evidencing the peculiarities of international projects and the role of Big Five personality traits in this context. From a practical perspective, the results suggest that organizations should consider cultural intelligence as an important criterion in the selection and development of international project managers.